Efektivitas Ekstrak Daun Kangkung (Ipomoea aquatica Forsk.) sebagai Fungisida Nabati untuk Mengendalikan Jamur Colletotrichum capsici pada Buah Cabai - Pani, Mario; Efendi, Usman (JURNAL AGROPLASMA, 2022)
One obstacle in increasing the production of chili is the number of attacks Plant Pest Organisms (OPT), which can cause a loss both in quantity and quality. So necessary to control in order to minimize the risks. This study aims to determine the effectiveness of the spinach leaf extract in controlling anthracnose (Colletotrichum capsici) in the chilies. The experimental design used in this study is completely randomized design (CRD) pattern of non factorial consisting of 4 treatments and 4 replications for each treatmentÂ  in-vitro and in-vivo, so that for each in-vitro and in-vivo obtained 16 experimental units. The treatment is tested in this study consisted of 4 levels kale extract ie, 5%, 10%, 15% and 20%. In-vitro, the results showed that the leaf extract can inhibit the growth kale C.capsici colony diameter. Diameter lows seen in 20% extract treatment treatment is 28 mm. Meanwhile, in-vivo experiments showed that the mean diameter observations on the highest spot 7 HSA present in 5% of treatment of 7.8 mm and 7 mm at the lowest concentration of 20%. For the percentage of disease incidence and intensity of the disease show the results were not significantly different. It was concluded that the spinach leaf extract has not been able to control anthracnose in pepper fruit which is caused by C.capsici.Â Keywords: Extract, Vegetable, Colletotrichum capsici, Fruit chili.